The boy - Hoag, Tami (Dutton, 2018)
"When Detective Nick Fourcade enters the home of Genevieve Gauthier outside the sleepy town of Bayou Breaux, Louisiana, the bloody crime scene that awaits him is both the most brutal and the most confusing he's ever seen. Genevieve's seven-year-old son, KJ, has been murdered by an alleged intruder, yet Genevieve is alive and well, a witness inexplicably left behind to tell the tale. There is no evidence of forced entry, not a clue that points to a motive. Meanwhile, Nick's wife, Detective Annie Broussard, sits in the emergency room with the grieving Genevieve. A mother herself, Annie understands the emotional devastation this woman is going through, but as a detective she's troubled by a story that makes little sense. Who would murder a child and leave the only witness behind? When the very next day KJ's sometimes babysitter, twelve-year-old Nora Florette, is reported missing, the town is up in arms, fearing a maniac is preying on their children. With pressure mounting from a tough, no-nonsense new sheriff, the media, and the parents of Bayou Breaux, Nick and Annie dig deep into the dual mysteries. But sifting through Genevieve Gauthier's tangled web of lovers and sorting through a cast of local lowlifes brings more questions than answers. Is someone from Genevieve's past or present responsible for the death of her son? Is the missing teenager, Nora, a victim, or something worse? Then everything changes when Genevieve's past as a convicted criminal comes to light"--